Fitness Change and Subsequent Academic Performance in Adolescents. (23rd July 2013) - Chen, Li‐Jung; Fox, Kenneth R.; Ku, Po‐Wen; Taun, Chih‐Yang
ABSTRACT: BACKGROUND: This study examined the association between fitness change and subsequent academic performance in Taiwanese schoolchildren from 7th grade to 9th grade. METHODS: The 7th graders from 1 junior high school district participated in this study (N = 669). Academic performance was extracted from school records at the end of each grade. Cardiovascular (CV) fitness, sit‐and‐reach flexibility, bent‐leg curl‐ups, and height and weight for calculating body mass index (BMI) were assessed at the start of each grade. RESULTS: The results showed that improvement in CV fitness, but not muscular endurance or flexibility, is significantly related to greater academic performance. A weak and nonsignificant academic‐BMI relationship was seen. CONCLUSION: CV fitness exhibits stronger longitudinal associations with academic performance than other forms of fitness or BMI for adolescents.